If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 4)(4x + -7) = 0 Reorder the terms: (4 + 7x)(4x + -7) = 0 Reorder the terms: (4 + 7x)(-7 + 4x) = 0 Multiply (4 + 7x) * (-7 + 4x) (4(-7 + 4x) + 7x * (-7 + 4x)) = 0 ((-7 * 4 + 4x * 4) + 7x * (-7 + 4x)) = 0 ((-28 + 16x) + 7x * (-7 + 4x)) = 0 (-28 + 16x + (-7 * 7x + 4x * 7x)) = 0 (-28 + 16x + (-49x + 28x2)) = 0 Combine like terms: 16x + -49x = -33x (-28 + -33x + 28x2) = 0 Solving -28 + -33x + 28x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -7x)(7 + -4x) = 0Subproblem 1
Set the factor '(-4 + -7x)' equal to zero and attempt to solve: Simplifying -4 + -7x = 0 Solving -4 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -7x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -7x = 0 + 4 -7x = 0 + 4 Combine like terms: 0 + 4 = 4 -7x = 4 Divide each side by '-7'. x = -0.5714285714 Simplifying x = -0.5714285714Subproblem 2
Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75Solution
x = {-0.5714285714, 1.75}
| 25+75+-90=35 | | x^7+8=-64 | | (3x+5)(x-9)= | | 11x-8=24 | | -16=7b+12 | | 8x+6=0.75 | | (3x-4)(2x+3)=0findx | | 11x-7=0.64 | | 4x+2=1.5 | | 5x+6x-4x=23 | | 9x-9=1.22 | | 5x-2forx=7 | | 2x*lnx= | | 8x+6y=-30 | | 25-55+(85+45)= | | 3y-4x=-15 | | 55x+7y=400 | | logx(3x^2-17x+72)=1 | | 10x=16x-48 | | (s^2-3s+1)(2s+1)= | | (5-4)(-3-6)+(14-3)(5+11)= | | x^3-7x^2-8x+44=0 | | 4h-14h+2=72 | | 3x^2+x-2=x | | 12x^2-16x+1=0 | | 0.03x+6.5=5.66 | | 5sinx-3cosx=o | | 8x-72=-4x | | 2(a+1)+4(3a+5)=64 | | -12=x+6y | | 25+-55+(85+65)=5x | | 5y-40=5x |